2022
DOI: 10.1186/s12906-022-03733-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of endophytic actinobacterium associated with Aloe ferox mill for antibacterial activity

Abstract: Background The emergence of drug resistance among pathogens has resulted in renewed interest in bioprospecting for natural microbial products. Methods This study aimed to bioprospecting endophytic actinobacterium associated with Aloe ferox Mill for its antibacterial activity. Endophytic actinomycetes were isolated from the gel of A. ferox Mill by surface sterilization technique using actinomycete isolation agar. The isolate with a promising antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Thus, the disturbance of the respiratory chain dehydrogenase can result in insufficient energy production and supply, consequently leading to the bacterial inhibition and/or death [ 43 ]. In this study, the extract showed destructive properties against the respiratory chain dehydrogenase, implying that the bacteria’s energy production pathway was affected, consequently leading to the inhibition and/or killing of the selected bacterial strains [ 44 ]. The results are in agreement with the findings by Gomaa, [ 45 ], whereby the antimicrobial compounds were able to exert their efficacies by tempering with the activity of bacterial respiratory chain dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the disturbance of the respiratory chain dehydrogenase can result in insufficient energy production and supply, consequently leading to the bacterial inhibition and/or death [ 43 ]. In this study, the extract showed destructive properties against the respiratory chain dehydrogenase, implying that the bacteria’s energy production pathway was affected, consequently leading to the inhibition and/or killing of the selected bacterial strains [ 44 ]. The results are in agreement with the findings by Gomaa, [ 45 ], whereby the antimicrobial compounds were able to exert their efficacies by tempering with the activity of bacterial respiratory chain dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…The plant environment is considered an untapped niche because only 1% of the total population of microbes residing in it has been explored so far, and the majority of them (70%) are identified as fungi 7 . Bioprospecting for endophytic actinomycetes in plants is of particular interest since the plants may possess a unique internal environment 8 that may support the production of compounds with novel chemical structures 6 .…”
Section: Introductionmentioning
confidence: 99%